Sanctions, Accommodation, and Defiance. A Long Track of US Sanctions Targeted at Iran. Radosław Fiedler’s Interview with Richard Nephe - Fiedler, Radosław (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
Interview